(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
This study uses a research method, with the type of empirical research. The types and sources of data used in this study are primary data and secondary data. To get the required data, the researcher collected data through three collection methods, namely interviews, observation, and documentation. And the data obtained both primary and secondary legal materials were analyzed qualitatively and then presented descriptively. The results of this study indicate that land is part of the Earth’s surface which contains natural resources that must be utilized and must also be protected. In its utilization, especially business actors and the community always prioritize concern for the land and its wealth so that not only can the benefits be taken, but also can protect and pay attention to the preservation of the environment.